Brewer's spent grain and corn steep liquor as alternative culture medium substrates for proteinase production by Streptomyces malaysiensis AMT-3 - Rodrigo Pires do Nascimento (Brazilian Journal of Microbiology, 2011)
Brewer's spent grain and corn steep liquor or yeast extract were used as the sole organic forms for proteinase production by Streptomyces malaysiensis in submerged fermentation. The influence of the C and N concentrations, as well as the incubation periods, were assessed. Eight proteolytic bands were detected through gelatin-gel-electrophoresis in the various extracts obtained from the different media and after different incubation periods, with apparent molecular masses of 20, 35, 43, 50, 70, 100, 116 and 212 kDa. The results obtained suggest an opportunity for exploring this alternative strategy for proteinases production by actinomycetes, using BSG and CSL as economically feasible substrates.